Evaluasi Implementasi Sistem Penyimpanan Obat di Apotek - Puput Astreawati; Yulianis Yulianis; Medi Andriani (Jurusan Farmasi Universitas Negeri Gorontalo, 2022)
Improper or inefficient storage makes expired drugs undetected can cost pharmacies. Therefore, in the selection of a storage system, it must be selected and adapted to the existing conditions so that drug services can be carried out in an effective and efficient manner. The purpose of this study is to see the drug storage system based on storage standards at the Jambi City Pharmacy. This study uses a descriptive observational method by making observations (direct observations). Data collection is done by the checklist method. The population of this research is pharmacies in 8 districts of Jambi city. The sample of this research is pharmacies who are willing to give research permits, with a total of 1 pharmacy in 1 sub-district. This research was conducted from May 2021 to July 2021.The results of the research on the study of the implementation of the drug storage system at the Jambi City Pharmacy, namely facilities and infrastructure for drug storage with good criteria 6 pharmacies and very good 2 pharmacies, storage standards with very good criteria in all pharmacies, high alert drug storage with poor criteria in all pharmacies, storage of certain drugs/drug ingredients with very good criteria in all pharmacies The results of this study can be concluded that the drug storage system in Jambi City pharmacies has good criteria 6 pharmacies and 2 pharmacies are very good.